Prenatal‐onset of congenital neuronal ceroid lipofuscinosis with a novel CTSD mutation. Issue 18 (7th September 2021) - Chartier, Suzanne; Boutaud, Lucile; Le Guillou, Edouard; Alby, Caroline; Billon, Clarisse; Millischer, Anne‐Elodie; Caillaud, Catherine; Galmiche, Louise; Mechler, Charlotte; Sonigo, Pascale; Boddaert, Nathalie; Lyonnet, Stanislas; et al.
Abstract: Background: Neuronal ceroid lipofuscinoses (NCLs) form a clinically and genetically heterogeneous group of inherited neurodegenerative disorders that share common neuropathological features. Although they are the first cause of neurodegenerative disorders in children, their congenital forms are rarely documented. They are classically due to mutations in the CTSD gene (the CLN10 disease). Affected newborns usually present severe microcephaly, seizures and respiratory failure leading to death within the first postnatal days or weeks. Cases: We report on two siblings, in which exome sequencing identified a novel homozygous CTSD variant. The first sib presented at birth with seizures, rapidly progressive postnatal microcephaly and visual deficiency related to retinal dysfunction. Progressive neurological deterioration leads to death at the age of 24 months. Cathepsin D activity was reduced in the cultured fibroblasts of this patient. The second sib, a fetus of 36 weeks of gestation, was delivered after pregnancy termination for brain abnormalities (in accordance with French Legislation) suggesting a recurrence of the disease. Fetal postmortem examination disclosed neuropathological features consistent with NCL. Conclusions: Congenital NCL related to CTSD mutations is a neuronal storage disorder that produces in the developing brain diffuse neurodegeneration and white matter atrophy resulting in a progressive and rapidly lethal microcephaly.